Sleep quality, chronotype and metabolic syndrome components in bipolar disorders during the remission period: Results from the FACE-BD cohort. (14th September 2017) - Godin, Ophélia; Henry, Chantal; Leboyer, Marion; Azorin, Jean-Michel; Aubin, Valerie; Bellivier, Frank; Polosan, Mircea; Courtet, Philippe; Gard, Sebastien; Kahn, Jean-Pierre; Loftus, Josephine; Passerieux, Christine; et al.
ABSTRACT: Data on sleep or circadian abnormalities and metabolic disturbances in euthymic bipolar disorders are scarce and based on small sample sizes. The aim of this study was to explore the associations between sleep disturbances, chronotype and metabolic components in a large sample of euthymic patients with bipolar disorders (BD). From 2009 to 2015, 752 individuals with bipolar disorders from the FACE-BD cohort were included and assessed for sleep quality, chronotype and metabolic components. The Structured Clinical Interview for DSM-IV Axis I Disorders (SCID) was used to confirm the diagnosis of BD. Subjective sleep quality was measured with the Pittsburgh Sleep Quality Index and chronotype with the Composite Scale of Morningness. Sociodemographic and clinical characteristics, psychotropic treatment, psychiatric comorbidities and blood samples were collected. In our sample, 22.4% of individuals with BD presented with a metabolic syndrome, 53.7% had sleep disturbances, 25.4% were considered as having an evening chronotype and 12.6% as having a morning chronotype. Independently of potential confounders, euthymic patients with sleep disturbances had a higher abdominal circumference, and patients with evening chronotype had a significantly higher level of triglycerides. There was an association between evening chronotype and an increased atherogenic index of plasma (OR = 4.8, 95%CI = 1.6–14.7). Our findings contribute the scant literature on the relationship between sleep quality, chronotype and cardiometabolic components in euthymic individuals with BD and highlight the need to improve quality of sleep and patient education about healthier sleep-hygiene practices.